Construction and Validation of Simulated scenario for the development of Nursing Students Diagnostic Reasoning - Gouveia, Marcella Ferroni; Souza, Cristiane Chaves de; Braga, Luciene Muniz; Carvalho, Daniel Camilo de; Boscarol, Gabriela Tavares; Borges, Alessandra Bastos; Salgado, Patrícia de Oliveira (Ciência e Natura, 2021)
Objective: to describe the process of construction and validation of a clinical simulation scenario whose objective of the scenario was the development of diagnostic reasoning skills in nursing students. Method: this is a descriptive study of the process of construction and content validation of a clinical simulation scenario for the development of diagnostic reasoning skills in students of the fourth semester of the Undergraduate Nursing course. Results: The scenario was validated by eight experts in the area covered by the study. The level of agreement between the judges above 90% was considered. Conclusion: In order for clinical simulation to be effective, it is necessary to have prior planning and clear objectives. Following a practical theoretical-script facilitates the development of the scenario, favoring the student's learning process.